Bosnia and Herzegovina : Poverty Reduction Strategy Paper-Mid-Term Development Strategy-Joint Staff Assessment. (IMF Staff Country Reports; Country Report, 2005)
Bosnia and Herzegovina's Poverty Reduction Strategy paper reports that significant progress has been made since the late 1990s in building both a market economy and a single economic space. GDP growth has slowed recently following the post-conflict bounce, and the current account deficit of 18 percent of GDP in 2003 is well above levels associated with external sustainability. The slowdown in GDP growth has occurred even though GDP had not recovered to pre-war levels at the end of 2003.